Investigation of Plantktonic Diversity in Krishnagiri Reservoir, Krishnagiri District, Tamil Nadu, India - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In this present study, hydro biological characteristic features of the Krishnagiri reservoir Dam, the dates for the present study were collected from 3 sampling stations for the period of 6 months in both premonsoon and monsoon seasons. A total number of 44 Zooplankton and 14 Phytoplankton species were identified in the study area. Totally 6 groups of Zooplankton such as Rotifer, Copepod, Cyclops, Ostracod, Protozoan and Insect were observed during the study period. With regards to zooplankton, a total number of 44 species were recorded under the group during the study period. The genus Brachionus and Lecane were dominant over the other species. Among different groups, Brachionus ranked first out of 35 followed by Lecane with 2 species. In the present study, it is noted that whenever two or more species of a genus occurred, only one species was dominant.